Transforming Investment Structures in Capital-Intensive Electricity Utilities: A Managed Service Approach for CapEx-to-OpEx Transformation - Ignatius Rendroyoko; Najahul Imtihan; Ishak Sinaga (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
Electric utilities operate in a capital-intensive environment characterized by substantial infrastructure investment requirements, long asset life cycles, regulated tariffs, and relatively stable financial returns. Increasing electricity demand and energy transition initiatives have intensified the need for alternative financing mechanisms that support infrastructure expansion while maintaining service reliability and affordability. This study evaluates the transformation of conventional Capital Expenditure (CapEx)-based investment structures into Operating Expenditure (OpEx)-based arrangements through managed service models in electricity utilities. Using a mixed-method explanatory case study and techno-economic analysis, the study examines managed service implementation for 160 kVA distribution transformers in Indonesia's electricity distribution sector. The analysis incorporates lifecycle cost evaluation, cash flow assessment, and financial indicators including Net Present Value (NPV) and Internal Rate of Return (IRR). The results show that the managed service model improves financial flexibility by replacing large upfront investments with predictable periodic payments and transferring operational risks to service providers. However, this flexibility is accompanied by an approximately 15% increase in lifecycle NPV compared with the conventional Total Expenditure (TOTEX) model. These findings demonstrate that managed services represent a viable alternative financing strategy for capital-intensive electricity utilities facing investment constraints